PENINGKATAN KEMAMPUAN MEMBACA SISWA DALAM MEMAHAMI RECOUNT TEKS MENGGUNAKAN TEKNIK “SUMMARIZING” PADA SISWA KELAS X - 7 SMA NEGERI 17 SURABAYA: SMA NEGERI 17 SURABAYA - FIANICO SUKMANA ROZY INTAN MAULIDA QORRY, AINA (Mitra Pendidikan, 2021)
English proficiency is a necessity and necessity in the current era of communication and globalization, however, the existing learning still produces scores below the Minimum Completeness Criteria (KKM). This phenomenon occurs because the student learning process is very passive. So that the emergence of a feeling of insecurity in students. To overcome this problem, a learning innovation is needed so that student learning outcomes are better. Building a more meaningful learning atmosphere by making students more involved is a learning innovation that continues to be developed. One way to build a meaningful learning atmosphere is to use the "Summarizing" technique to understand Recount Text. So this research has the aim of wanting to find out whether there is an increase in reading skills in understanding recount text using the Summarizing technique. This research is a Classroom Action Research (PTK). From the results of data analysis in this study, it was found that the "Summarizing" technique could improve students' reading skills. The "Summarizing" technique is also able to make students more motivated to read with the aim of being able to understand the content of the reading and finally, students are more skilled in choosing words to be used to summarize the content of the reading..